Literacy of Cold Medication Labeling among Patient with Hypertension in Indonesia - Kristina, Susi Ari (Asian Journal of Pharmaceutics (AJP), 2019)
Introduction: Non-prescription medication is relatively safe but not risk free and can lead to serious adverse drug events if used without attention to the information printed on the label. Medication literacy includes the ability to read and comprehend medication label. The aim of the study was to describe health literacy focused on the ability to read cold medication label and identify factors that associated with it among patient with hypertension in Sleman District, Yogyakarta Province, Indonesia. Materials and Methods: A cross-sectional questionnaire was developed and validated. In-person interviews include a literacy assessment which was conducted among 109 respondents in five primary health centers in Sleman District, Yogyakarta Province, Indonesia, during September –December 2017. A convenience sampling technique was used. Respondents were asked to read information printed on the cold medication label. The correct information was assessed and categorized. Descriptive statistic and Chi-square test were used in the analysis. Results: Most of the respondents read the name of medicine and indications correctly. More than half of the respondents mispronounced to active ingredients (69.7%). Respondents were not able to read dosage (74.3%), frequency of intake (54.1%), side effects (83.5%), and contraindications (89.0%). There were 85.3% respondents categorized into illiterate. The correct sentence: Education level was associated with the ability to read medication label (P = 0.038). Conclusion: This study found that ability patients on reading medication label need to be improved. Information on medication label majority printed on small font size caused patients inability to read medication label correctly. Key strategies to improve readability of medication labels should be developed.